Incumbency, party identity and governmental lead: Evidence for heterogeneous incumbency effects for Germany - Florian Ade; Ronny Freier; Christian Odendahl (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Do incumbents in an election have an advantage, and if so, are these advantages heterogeneous across parties or government and opposition? We first present a theoretical discussion on the possible heterogeneity of incumbency effects in a pure two-party system. Then, we estimate the incumbency effect for the direct district candidates in German federal and state elections using a regression discontinuity design (RDD). When studying the heterogeneity in these effects, we find that incumbents from both large parties, the center-right CDU and the center-left SPD, have an advantage only if the SPD is in government. This effect is robust and shows even in state elections that are unrelated to federal elections - calling into question the findings of average incumbency effects in the literature. Because this effect is stronger in the East than in the West and only shows post reunification, we hypothesise that the emergence of the socialist party The Left may be behind this heterogeneity.
Keywords: H10; H11; H77; 330; incumbency advantage; regression discontinuity design; federal elections; state elections